The Search for a Social Ideal as a Cultural Tradition of Russian Thought - Matveeva, Natalya (Slavica, 2022)
This study investigates some important lines of Russian social thought of the 19th and early 20th centuries in the context of the interpretation of the social ideal. Four perspectives of the problem are outlined: the first one is cultural geographic, divided into three branches (Westernism, Slavophilism and, Eurasianism), the second one is sociological positivism, the third one is philosophical liberalism, and the fourth one is religious thought. The cultural-geographic orientation created  a wide field of the work of social thought in studying the paths of social development. Sociologists positivists P. Lavrov and N. Mikhailovsky, who were founders of ‘narodnichestvo’ movement, formulated the notion of social ideal as an object of sociological research. The positivist perspective that was intended for the ideals of social solidarity, transformed into the left the traditionalism that was narodnichestvo ideology. Narodnichestvo created the ideal prerequisites for the dissemination of  Marxism in Russia. Liberal philosophic thought offered the original concept of the development of personality as a social ideal (P. Novgorodtsev). The fourth perspective was closest to the modern comprehension of the processes of unification of humankind and the development of the world economic system. The issue of social ideal thus became the main tradition of thought in the pre-revolutionary Russia.